2012
DOI: 10.1002/ange.201204923
|View full text |Cite
|
Sign up to set email alerts
|

Amidocuprates for Directed ortho Cupration: Structural Study, Mechanistic Investigation, and Chemical Requirements

Abstract: Gilman‐ und Lipshutz‐Amidocuprate wurden einer röntgenkristallographischen Analyse unterzogen, die darauf hindeutet, dass die Gegenwart von LiX (X=CN, I) und THF das Gleichgewicht zugunsten der Lipshutz‐Cuprate verschiebt und wichtig für die Erzeugung der aktiven Spezies in dirigierten ortho‐Cuprierungen ist. Dichtefunktionalrechnungen bescheinigen monomeren Gilman‐Cupraten eine beispiellos hohe Reaktivität (siehe Schema, DG=dirigierende Gruppe).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…[ 5 ] Recent advances have revealed so-called Gilman-type monomers and dimers[ 6 ] and (in line with theory)[ 7 ] heteroleptic monomers[ 8 ], [ 9 ] and dimers (Figure 1 a , b, d). [ 10 ] Conversely, cyanide-containing Lipshutz cuprates[ 11 ] with heteroaggregate structures have now been elucidated (Figure 1 e ),[ 3 ] with very recent work proving that the replacement of X=CN by X=halide affords structurally analogous complexes,[ 4c , d , 6 ] and suggesting use of the term Lipshutz-type to describe this wider group of comparable cuprates. Interestingly, although the reactivity of Lipshutz-type cuprates has been considered to often exceed that of their Gilman-type counterparts,[ 4b , 8 , 13 ] it was recently suggested that a Lipshutz-type reagent could be used to generate a more reactive Gilman-type intermediate in situ.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…[ 5 ] Recent advances have revealed so-called Gilman-type monomers and dimers[ 6 ] and (in line with theory)[ 7 ] heteroleptic monomers[ 8 ], [ 9 ] and dimers (Figure 1 a , b, d). [ 10 ] Conversely, cyanide-containing Lipshutz cuprates[ 11 ] with heteroaggregate structures have now been elucidated (Figure 1 e ),[ 3 ] with very recent work proving that the replacement of X=CN by X=halide affords structurally analogous complexes,[ 4c , d , 6 ] and suggesting use of the term Lipshutz-type to describe this wider group of comparable cuprates. Interestingly, although the reactivity of Lipshutz-type cuprates has been considered to often exceed that of their Gilman-type counterparts,[ 4b , 8 , 13 ] it was recently suggested that a Lipshutz-type reagent could be used to generate a more reactive Gilman-type intermediate in situ.…”
mentioning
confidence: 62%
“…Structural organocuprate(I) chemistry was recently the subject of review. [ 5 ] Recent advances have revealed so-called Gilman-type monomers and dimers[ 6 ] and (in line with theory)[ 7 ] heteroleptic monomers[ 8 ], [ 9 ] and dimers (Figure 1 a , b, d). [ 10 ] Conversely, cyanide-containing Lipshutz cuprates[ 11 ] with heteroaggregate structures have now been elucidated (Figure 1 e ),[ 3 ] with very recent work proving that the replacement of X=CN by X=halide affords structurally analogous complexes,[ 4c , d , 6 ] and suggesting use of the term Lipshutz-type to describe this wider group of comparable cuprates.…”
mentioning
confidence: 65%
See 3 more Smart Citations